Yang-Baxter integrable Lindblad equations - Aleksandra A. Ziolkowska, Fabian H.L. Essler (SciPost Physics, 2020)
We consider Lindblad equations for one dimensional fermionic models and quantum spin chains. By employing a (graded) super-operator formalism we identify a number of Lindblad equations than can be mapped onto non-Hermitian interacting Yang-Baxter integrable models. Employing Bethe Ansatz techniques we show that the late-time dynamics of some of these models is diffusive.